Epidemiology and management of massive, sub-massive, and non-massive pediatric pulmonary embolism: a systematic reviews - Mohammed Alsabri; Dina Essam Abo-elnour; Mohammed Ayyad; Mahmoud Shaaban Abdelgalil; Basel F. Alqeeq; Muhammad Azan Shahid (BMC Pediatrics)
Abstract Objective To evaluate the current evidence on the diagnosis, management, and outcomes of pediatric pulmonary embolism (PE) across varying severity classifications, including massive, submassive, and non-massive presentations. Methods A systematic review was conducted following PRISMA guidelines. Searches were performed in PubMed, Scopus, Web of Science, and Cochrane databases up to February 17, 2024. Eligible studies included pediatric and adolescent patients (≤ 21 years) with confirmed PE diagnoses. Risk of bias was assessed using the NIH tool. Results Six studies involving 258 pediatric patients with massive, submassive, or non-massive PE were included. Most patients were adolescents, with a mean age of 14.1 years and a predominance of females (62–66%). Risk factors included obesity, oral contraceptive use, thrombophilia, and autoimmune conditions. Computed tomography pulmonary angiography (CTPA) was the most frequently used diagnostic modality, showing varied lobar, segmental, and subsegmental involvement. Management strategies ranged from anticoagulation to catheter-directed thrombolysis and surgical thrombectomy. Outcomes varied by severity, with massive PE cases showing higher mortality and complications compared to submassive and non-massive cases. Conclusion Pediatric PE requires tailored risk stratification and management strategies to optimize outcomes. Delays in diagnosis and severe disease presentations contribute to higher morbidity and mortality. Future research should focus on standardized severity classifications, novel diagnostic modalities, and comparative assessments of therapeutic interventions to enhance outcomes in this population.